1986
DOI: 10.1002/jmor.1051880206
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure of the ileum of Locusta migratoria

Abstract: The epithelium of the ileum of Locusta migratoria is composed of a single layer of columnar cells surrounded on the luminal side by cuticle and on the haemocoel side by a circular muscle layer. Where the circular muscles contact the epithelium, longitudinal muscles are present and the epithelium is slightly reduced. Elsewhere, a subepithelial sinus separates the epithelium from the circular muscle layer. The epithelial cells are characterised by extensive infoldings of the apical and basal cell membranes, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0
1

Year Published

1992
1992
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 20 publications
2
11
0
1
Order By: Relevance
“…This structure resembles the "apical complex" of the rectal papillae of the termite (Noirot and Noirot-Timothée, 1977) and cockroach (Noirot and Noirot-Timothée, 1976). Similar structures have also been reported in the anterior portion of the hindgut of the termite and Locusta (Yamaoka and Nagatani, 1978;Peacock, 1986). The apical complex is thought to be involved in ATP-dependent ion or water transport.…”
Section: Resultssupporting
confidence: 67%
“…This structure resembles the "apical complex" of the rectal papillae of the termite (Noirot and Noirot-Timothée, 1977) and cockroach (Noirot and Noirot-Timothée, 1976). Similar structures have also been reported in the anterior portion of the hindgut of the termite and Locusta (Yamaoka and Nagatani, 1978;Peacock, 1986). The apical complex is thought to be involved in ATP-dependent ion or water transport.…”
Section: Resultssupporting
confidence: 67%
“…Vesicles partially filled with electron-dense materials of concentric arrangement, vesicles containing an amorphous particulate material and electron-lucent vesicles were found in the cytoplasm of types I and II cells of the Malpighian tubules of B. morio . We suggest that the interior of these vesicles were fully occupied by spherocrystals, however their content may be lost during histological procedures, resulting in the formation of vesicles with different degrees of spherocrystals dissolution (Berridge & Oschmann, 1969; Bell & Anstee, 1977; Peacock, 1986; Garayoa et al, 1992).…”
Section: Discussionmentioning
confidence: 94%
“…Type I cells of the ileum of B. morio did not exhibit features of cells involved in absorption, like the small cells in the ileum of L. migratoria (Peacock, 1986). However, well-developed rough endoplasmic reticulum, euchromatic nucleus, and larger vesicles in the apical region suggest that type I cells may play a role in the secretion of protein, as reported for the ant Cephalotes atratus (Bution & Caetano, 2010).…”
Section: Discussionmentioning
confidence: 97%
“…This ultrastructure suggests that the colon is not a major site of ion and fluid reabsorption. In contrast, the epithelial cells of the ileum possess extensive apical and basal infoldings that are closely associated with numerous mitochondria, indicative of an epithelium that carries out transport (Peacock, 1986). Using an everted cannulated sac of the locust rectum, Goh and Phillips (Goh and Phillips, 1978) determined that the absorption rate of ions (Na + , Cl − , K + ) and water did not significantly change after the first hour and remained steady for 4 h. The SIET-measured K + fluxes at the ileum utilizing the semi-intact gut preparation showed that these fluxes remained consistent for at least 1.5 h, which was the maximum length of time required to carry out the experiments.…”
Section: Research Articlementioning
confidence: 99%
“…For instance, developmentally, the foregut arises from ectoderm and is lined by relatively impermeable cuticle, making storage a primary function of this region and absorption difficult (Dow, 1987). The hindgut also originates from ectoderm, but the cuticular lining of the hindgut is far more permeable than the foregut (Maddrell and Gardiner, 1980), allowing this region to carry out ion and water transport (Hanrahan and Phillips, 1983;Peacock, 1985;Peacock, 1986). The epithelial cells of the colon possess short apical microvilli with mitochondria residing at their base but not in close association (Peacock, 1985).…”
mentioning
confidence: 99%